2017
DOI: 10.1039/c7ra01571b
|View full text |Cite
|
Sign up to set email alerts
|

Surface characteristics influencing bacterial adhesion to polymeric substrates

Abstract: Effective surface area on rough substrates for bacterial adhesion is examined by analyzing the solid area fraction of surfaces, where the bacterial medium is in contact with the solid surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
240
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 342 publications
(281 citation statements)
references
References 40 publications
13
240
2
Order By: Relevance
“…However, we observed the opposite relationship between contact angle and surface smoothness when parylene was compared to polyurethane. This may imply that the bacterial resistance clearly observed in the experiment may be due to other material properties known to impact bacterial adhesion and biofilm formation, such as surface energy, surface charge, and surface topology 23 …”
Section: Discussionmentioning
confidence: 99%
“…However, we observed the opposite relationship between contact angle and surface smoothness when parylene was compared to polyurethane. This may imply that the bacterial resistance clearly observed in the experiment may be due to other material properties known to impact bacterial adhesion and biofilm formation, such as surface energy, surface charge, and surface topology 23 …”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, hydrolysis led to a higher surface hydrophilicity, as WCA measurements shown. This has been speculated to hinder bacterial adhesion by making decrease hydrophobic interactions and enhancing a substrate‐bacteria repulsion . On the other hand, hydrolysis implies the incorporation of negative surface charges that may result into reduced bacteria attachment, as a consequence of the electrostatic repulsion between E. coli , with an overall negative charge, and the functionalized substrates …”
Section: Resultsmentioning
confidence: 99%
“…In addition to the surface energy, hydrophobicity of the substratum also appears to affect bacterial attachment. In a study carried out by Yuan et al, surfaces with moderate hydrophobicity (water contact angle of about 90°) were shown to lead to highest bacterial adhesion . In another study, Quirynen et al demonstrated that biofilms were found to form less on hydrophobic surfaces than on hydrophilic surfaces in oral environments .…”
Section: Device‐associated Infectionsmentioning
confidence: 99%
“…Although the trend was further confirmed in several other studies, it was primarily based on thermodynamics. The inability of the model to recognize the complexities of bacterial structures as well as specific interactions between materials and bacteria, such as those mediated by MSCRAMMs, have caused some deviations from the model prediction …”
Section: Device‐associated Infectionsmentioning
confidence: 99%